Diurnal dynamics of different circadian transcription modules in Chinese pine needles and roots during dormancy induction - Junhe Yang; Kai Qu; Huili Wang; Yousry A. El-Kassaby; Wei Li (BMC Plant Biology)
Abstract Winter dormancy ensures that trees in temperate zones respond appropriately to environmental variations, thereby enhancing their adaptability and resilience. In the northern hemisphere, the dormancy of conifers is induced by short-day and cold temperature. Previous studies have revealed that TFL2 is a key regulator involved in conifers’ bud set and growth cessation during the dormancy-induced phase. Based on the annual expression profile analysis of PtTFL2 in Chinese pine (Pinus tabuliformis Carr.), we identified key time nodes for dormancy initiation in autumn. To provide insight of the diurnal transcriptome dynamic in needles and roots during dormancy introduction, RNA-seq was performed at 12 consecutive time points in 24 h under natural environment in P. tabuliformis. Interestingly, we found that both needles and roots have rhythmic oscillatory genes, even though the roots could not receive light signals directly. We applied weighted gene co-expression network analysis (WGCNA) to integrate differentially expressed genes between needles and roots at different time points into highly correlated gene modules. Although the two modules are subject to different transcriptional controls during dormancy, both contain 35 identical transcriptional regulators. Some transcriptional factors with functional similarities and synergistic effects were found to play a role in the regulatory pathway, which provided some data support for mining gene functions and analyzing related regulatory pathways. Our results provide new insights into the molecular regulatory mechanisms involved in pine dormancy.